A Parallel Journeys Perspective on Technology-Supported Depression Care for Patients with Cancer - Suh, Jina; Bauer, Amy M.; Fann, Jesse R.; Fogarty, James; Hsieh, Gary; Williams, Spencer (CHI 2020 Workshop on Technology Ecosystems: Rethinking Resources for Mental Health, 2020)
Depression is common but under-treated in patients with cancer. Although support for management of co-morbid cancer and depression has been proposed through integration of psychosocial care into cancer services and through technology to support such care models, challenges remain in designing appropriate and usable technology interventions that meet the needs of the patients and their care team. Because patients with co-morbid cancer and depression struggle to navigate between their cancer care and psychosocial care journeys, traditional psychosocial approaches and mental health technologies need to be adapted to these experiences. In this workshop position paper, we describe our research designing technology to support depression care for patients with co-morbid cancer and depression through use of a parallel journeys framework. We propose that the design of mental health technology ecosystems should consider the multiple care journeys that an individual is navigating and present design implications for discussion in this workshop.